Illustrated aesthetic, class discourses and music education in schools in the early Twentieth century - Bolaño Amigo, María Eugenia (Historia y Memoria de la Educación, 2016)
The Concept of «serious music» has been subject to kinds of representations, especially since the Renaissance, which conditioned and continue to condition approaches to musical education as well as the socio-cultural constructions deriving from them. Thus, the underlying discourses regarding this notion of «music» still prevailed even with the notable innovations introduced in the early twentieth century in the area of music education, innovations which also had a major impact on the methodologies used in music class. Based on these considerations, we attempt to offer an approximation to the processes that, during the late nineteenth and early twentieth centuries, tended to support the idea of «serious music» while we also examine the influence they had on school educational history